Comparative study on fast pyrolysis of agricultural straw residues based on heat carrier circulation heating. (January 2019) - Fu, Peng; Yi, Weiming; Li, Zhihe; Li, Yongjun
Highlights: Fast pyrolysis of crop straws was explored based on ceramic ball circulation heating. Quadratic model was developed to correlate the CLR and HLR with bio-oil yield. For a given HLR above 1.12, bio-oil yield constantly increased as the CLR increased. Compared with CS, phenols content in bio-oils decreased by 9.9%, 14.3% for MS and RS. Abstract: Fast pyrolysis of agricultural straw residues based on ceramic ball circulation heating was studied by using an originally developed V-shaped drop tube pyrolysis unit. The yields of bio-oil, bio-char and pyrolysis gas from these straw residues were in the range of 41–46, 26–30 and 26–29 wt%, respectively, with maize straw giving the highest bio-oil yield. A quadratic model was developed to correlate the cellulose-to-lignin-ratio (CLR) and hemicellulose-to-lignin-ratio (HLR) with bio-oil yield. For a given HLR above 1.12, the bio-oil yield continued to increase as the CLR increased. However, when the HLR was between 0.86 and 1.12, it tended to decrease first and then increase with the increase of CLR. In contrast with CS, the proportions of acids and ketones in the bio-oils increased by 13.3% and 14.8% for MS and 9.2% and 30.5% for WS, respectively, while the proportion of phenols decreased by 9.9% and 14.3%.